A Thermodynamic, kinematic and microphysical analysis of a jet and gigantic jet‐producing Florida thunderstorm. Issue 16 (18th August 2015) - Lazarus, S. M.; Splitt, M. E.; Brownlee, James; Spiva, Nicholas; Liu, Ningyu
Abstract This paper presents a meteorological analysis of a storm that produced two jets, four gigantic jets (GJ), and a starter, which were observed by two radars as well as the Kennedy Space Center 4‐Dimensional Lightning Surveillance System on 3 August 2013 in Central Florida. The work is the first application of dual polarization data to a jet‐producing storm and is the fifth case related to a tropical disturbance. The storm environment is consistent with the moist tropical paradigm that characterizes about three quarters of the surface and aircraft observed jet and GJ events. The most unstable (MU) convective available potential energy is not unusual for Florida summer convection and is below the climatological mean for these events. An unusual speed shear layer is located near the storm equilibrium level (EL) and the storm exhibits a tilted structure with CGs displaced upshear. The turbulence, as measured by the eddy dissipation rate, is extreme near the storm top during the event window, consistent with the GJ mixing hypothesis. The individual events are collocated with, and track along, the center axis of the divergent outflow at the EL and occur within the region of the coldest GOES IR temperatures—placing the events within the overshoot. The dual polarization data indicate a deep graupel column, extending above the mixed phase layer, to a 13 km altitude.